Fisetin limits Chikungunya virus-induced apoptosis hallmarks in hepatocellular carcinoma cells - Rafidah Lani; Pouya Hassandarvish; Sazaly AbuBakar (Scientific Reports)
Abstract The study investigated the protective effects of fisetin on chikungunya virus (CHIKV)-induced apoptosis hallmarks in Huh7 cells. Fisetin significantly reduced CHIKV RNA levels and viral infectivity, outperforming Z-VAD-FMK and cisplatin. At 30 µM, fisetin markedly decreased (by > 90%) the number of infectious viral particles at 24 and 48 h post-infection (hpi). Fisetin also hindered CHIKV-induced DNA fragmentation, with the lowest levels observed in CHIKV-infected cells treated with fisetin compared to other treatments. Immunoblot analysis revealed that fisetin inhibited caspase-mediated PARP cleavage and significantly reduced cleaved PARP levels, indicating decreased apoptosis. Additionally, fisetin diminished the expression of cleaved caspase-3 and HSP-27 proteins, while restoring HIF-1α protein levels, suggesting a protective role against CHIKV-induced apoptosis. The study highlights the potential of fisetin as an effective antiviral agent against CHIKV through the modulation of apoptosis and oxidative stress pathways. These findings underscore the therapeutic promise of fisetin for treating CHIKV-induced apoptosis and warrant further investigation to explore its clinical applications and optimize its use in antiviral therapy.